2014
DOI: 10.1136/gutjnl-2014-307618
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal steroidogenesis controls PPARγ expression in the colon and is impaired during ulcerative colitis

Abstract: These results demonstrate cortisol control of PPARγ expression in CEC, highlighting cortisol production deficiency in colonocytes as a key molecular event in the pathophysiology of UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 35 publications
9
67
0
Order By: Relevance
“…In human tissue, CYP11A1 and CYP11B1 were detected in colonic biopsies suggesting that in physiological state the human mucosa is able to produce GC [29]. We recently confirmed and detailed this finding by showing expression of steroidogenic enzymes (3bHSD 1, 3bHSD 2, 11bHSD1) and cortisol production in colonic epithelial cells isolated from human surgical specimens [19].…”
Section: Evidence Of Intestinal Gc Productionmentioning
confidence: 59%
See 4 more Smart Citations
“…In human tissue, CYP11A1 and CYP11B1 were detected in colonic biopsies suggesting that in physiological state the human mucosa is able to produce GC [29]. We recently confirmed and detailed this finding by showing expression of steroidogenic enzymes (3bHSD 1, 3bHSD 2, 11bHSD1) and cortisol production in colonic epithelial cells isolated from human surgical specimens [19].…”
Section: Evidence Of Intestinal Gc Productionmentioning
confidence: 59%
“…Indeed, this was first demonstrated in vitro by Mueller and colleagues who showed that LRH 1 induces the CYP11A1 and CYP11B1 expression as well as corticosterone production in the murine intestinal epithelial cell line [40,42]. In human colon cancer cell lines, the down regulation of LRH 1 by small interfering RNA leads to the reduction of steroidogenic enzyme expression and cortisol synthesis [18,19]. In normal human colonic epithelial cells, the expression level of the mRNA encoding LRH 1 strongly correlates with the expression levels of 3bHSD and 11bHSD [19], suggesting that LRH 1 regulates intestinal GC synthesis under physiological state.…”
Section: Regulation Of Gc Production: From Adrenal To the Intestinementioning
confidence: 92%
See 3 more Smart Citations